USING THE METHOD OF NETWORK PLANNING AND MANADGEMENT IN THE PROCESS OF A CASH FLOW IMPROVEMENT OF MECHANISMS FOR BAGGAGE HANDLING IN AIR TRANSPORT - I. A. Ivanov; A. A. Bogatyrev (Научный вестник МГТУ ГА, 2016)
Introduction of innovative technologies in baggage handling will increase their reliability, will give an opportunity to start the transition to the new organizational and technological plans when developing new baggage handling systems to tackle urgent problems of airport development and improving the capacity of the real economic effect. Necessity of comparing costs with the resultant effect of the introduction of new methods of baggage handling determines the urgency of developing new methodological approaches to the justification of the effectiveness of innovative technology implementation baggage handling.